Aging Blunts Sympathetic Neuron Regulation of Motoneurons Synaptic Vesicle Release Mediated by β1- and α2B-Adrenergic Receptors in Geriatric Mice. (20th January 2020) - Wang, Zhong-Min; Rodrigues, Anna Carolina Zaia; Messi, María Laura; Delbono, Osvaldo
Abstract: This study was designed to determine whether and how the sympathetic nervous system (SNS) regulates motoneuron axon function and neuromuscular transmission in young (3–4-month) and geriatric (31-month) mice. Our approach included sciatic-peroneal nerve immunolabeling coregistration, and electrophysiological recordings in a novel mouse ex-vivo preparation, the sympathetic-peroneal nerve-lumbricalis muscle (SPNL). Here, the interaction between the motoneuron and SNS at the neuromuscular junction (NMJ) and muscle innervation reflect the complexity of the living mouse. Our data show that electrical stimulation of the sympathetic neuron at the paravertebral ganglia chain enhances motoneuron synaptic vesicle release at the NMJ in young mice, while in geriatric mice, this effect is blunted. We also found that blocking β-AR prevents the sympathetic neuron from increasing NMJ transmission. Immunofluorescence coexpression analysis of immunolabeled ARs with choline acetyltransferase-, tyrosine hydroxylase-, or calcitonin gene-related peptide immunoreactive axons showed that α2B-AR is found mainly in sympathetic neurons, β1-AR in sympathetic- and motor-neurons, and both decline significantly with aging. In summary, this study unveils the molecular substrate accounting for the influence of endogenous sympathetic neurons on motoneuron-muscle transmission in young mice and its decline with aging.